INTRODUCTION TO SPECIAL ISSUE 3 : 2014 - Mohamed, Mohamed Zin (PLANNING MALAYSIA, 2016)
Urban planning is a broad spectrum of subjects covering technical, social and political processes concerning with the control of the use of land and design of the urban environment. Local governance similarly extends its realm into areas such as urban management, institutional and capacity building, legal and regulatory mechanisms as well as accountability and transparency in the undertakings at the lowest level of administration. In view of these two research areas, diverse elements such as solving environmental issues through technical know-hows, coastal area management towards sustainability, speedier and smoother public services deliveries through the application of Information and Communication Technology (ICT) and community decision and governance, form parts of this book. Cities experiencing persistent problems such as increasing population, multiplicity in number of cities, air and noise pollution and traffic congestion have attracted many urban planners to come out with innovations and creative solutions to counter measure the effects of cities’ dynamisms. Local governance in Malaysia is expected to encounter many issues extending from the residential and community facilities allocation, threatened coastal areas’ management, public services delivery enhancement through Information and Communication Technology (ICT), legislative and regulative issues surrounding local governance, local economic generation through tourism promotion, to the more detailed climatic mapping and road geometrical design to resolved more specific localised issues. This edited book has addressed the above mentioned urban planning and local governance subjects in the eight chapters that it contains. The authors of chapter 1 explore the technical approaches of geospatial in a localised context. Urban governance resilience is mapped for the purpose of demarcating the urban morphology. The authors of chapter 2 have adopted a more fiscal and financial approach towards managing a degrading coastal area. In light of sustainable governance, the authors have managed to quantify various aspects of threats to sensitive coastal areas. In chapter 3, the authors focused on the application of ICT in public services delivery mechanism. E-payment deployments in the case studies of Majlis Bandaraya Shah Alam and Majlis Daerah Kampar have been cited as successful deliveries of local government services. Chapter 4 investigated the concept of satisfaction from the perspective of residential dwellers. The authors elaborated, quantified and analysed empirical evidences of satisfactory living conditions and environs. In chapter 5, the authors retrospectively reflected on the legal and institutional setting of various legislation related to urban planning and local governance. Historical setting and chronological development of each enactment processes are cited and discussed in great detail. The authors in chapter 6 discussed the positive impacts of tourism activities and expenditure on the local communities. Both direct and indirect benefits and economic impacts are quantified to model the actual community receipts from these travel and expenditure patterns. The case study of Melaka, a UNESCO world heritage site has been exemplified. In chapter 7, the authors mapped the changes in urban climate adopted in land use planning through the use of Geographic Information System (GIS). They reviewed such deployment in various planning documents and the effectiveness of such practices in the contemporary urban governance practice. Finally, at a localised context, the road geometric design has been investigated against the effectiveness of regulating speed on the arterial road by the authors of chapter 8. They concluded that whilst this regulation is purposively for discouraging the negative behaviour among drivers, effectiveness levels depended on the siting and location of such provision and strict adherence to the designs guidelines. In the end, it should be mentioned that although the eight chapters have addressed the important issues, directions and challenges of governing urban centres at the lowest level of administration through effective urban planning, these do not provide a complete spectrum of urban studies, implying that local governance is a derived part of sustainability, hence, it is a multifaceted and continuous process.